Transcendence at workplace scale: development and validation. Issue 4 (7th August 2020) - Khari, Chitra; Sinha, Shuchi
ABSTRACT: This paper explores the structural dimensions of Transcendence at Workplace (TAW) and develops and validates a measure for it. Transcendence at Workplace comprises of three correlated yet distinct dimensions: Work as service, Self-connectedness, and Sense of We-ness. Results establish the convergent, discriminant, criterion-related concurrent, and nomological validity of TAW. Findings confirm satisfactory reliability of the measure. This research makes a significant theoretical contribution to the evolving discourse on transcendence (in organizational context) by defining, developing, and validating the measure of Transcendence at Workplace. Practitioners can use the measure for assessing, and raising TAW, which will in turn have benefits for employees, organizations, and the larger community or society.